Pengaruh Kebijakan Deviden, Likuiditas, Manajemen Aset, dan Leverage Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Sektor Industri Food And Beverages yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2016-2020 - Anisa Nur Amalia Saputri Putri (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
This study aims to determine the impact of dividend policy, liquidity, asset management and leverage on firm value of food and beverage companies listed on the Indonesia Stock Exchange (IDX). There are inconsistencies in the results obtained from previous research and also the importance of company value for all parties. This study uses quantitative methods and data analysis techniques in this study, namely descriptive statistical analysis, panel data regression analysis, classical assumption test, hypothesis testing, and coefficient of determination with the Eviews 10 application. The population in this study, namely food and beverage companies, has been listed on the Indonesia Stock Exchange. 2016-2020 period. Determining the sample with the target sampling method using a total sample of 19 food and beverage companies and also the number of observations in this study, namely 95. Secondary data is the data used in this study. The method for collecting data is the documentation method from the IDX official website (www.idx.co.id). Test the hypothesis by t-test. With linear regression analysis of panel data with a significance level of 5%, the results of this study indicate that (1) dividend policy has a positive and significant impact in part on firm value (2) liquidity is also concluded that has a positive and significant impact on firm value, (3) Management assets have a positive and significant impact on firm value (4) Leverage also has a positive and significant impact on firm value (5) Dividend, liquidity, leverage and asset management policies have a significant positive impact on firm value at the same time.